2013
DOI: 10.3109/00016489.2013.850175
|View full text |Cite
|
Sign up to set email alerts
|

Is there a deafness duration limit for cochlear implants in post-lingual deaf adults?

Abstract: A marked improvement in the open-set speech perception scores (mono/disyllabic words and sentences) after implantation was seen in all groups, and no significant difference in the improvement in speech perception scores was observed among the groups. Age at onset of deafness was closely related to the postoperative performance, and patients who had lost their hearing before adolescence performed poorly.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
15
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 18 publications
2
15
1
Order By: Relevance
“…We performed multivariable regression analysis using the variables hierarchically proven to be predictive of post‐implant speech perception in earlier studies (e.g. age at implantation, age at onset of deafness, aetiology, duration of deafness, longest duration of deafness of either ear, pre‐implant best‐aided CVC score and PTA, gender and choice of ear) …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…We performed multivariable regression analysis using the variables hierarchically proven to be predictive of post‐implant speech perception in earlier studies (e.g. age at implantation, age at onset of deafness, aetiology, duration of deafness, longest duration of deafness of either ear, pre‐implant best‐aided CVC score and PTA, gender and choice of ear) …”
Section: Resultsmentioning
confidence: 99%
“…Due to large amounts of unknown aetiologies in previous studies, a clear pattern has not yet emerged between aetiology of deafness and post‐implant performance . Duration of deafness, or derived factors such as percentage of life deaf or age at onset of deafness, has shown a consistent correlation with post‐implant outcome, as well as pre‐implant speech perception tests . Contradictory results have been reported about the effect of an advanced age on speech perception performance …”
mentioning
confidence: 98%
See 2 more Smart Citations
“…In the meantime, Blamey et al [10] and Plant et al [11] reported that auditory improvement is inversely proportional to duration of deafness. Yet, Moon et al [12] reported data showing favorable auditory prognosis among patient that developed deafness after youth even with longer periods of sound deprivation.…”
Section: Introductionmentioning
confidence: 99%